The Impacts of Teachers’ Teaching Styles on High School Students’ Learning Engagement : An Example of English Class - Lan, Zirong (Transactions on Social Science, Education and Humanities Research, 2024)
As the golden learning time period in a lifetime, it is extremely crucial to investigate the influence mechanism of teaching styles on learning engagement to improve students’ learning engagement level in high school. By using the questionnaire method, this study aims to tap into the teacher’s standpoint on how to maximize the level of learning engagement of high school students by changing the teaching styles. This study found that there is a significant positive correlation between different teaching styles and students’ learning engagement. Besides, the degree of English learning motivation of high school students is most influenced by the extent of the teacher’s rigor and logic. The more caring and sharing the teacher is to high school student, the more energetic the student is in learning English. The more obvious the teacher’s rigorously logical style, the more concentrated the high school student’s learning is. Overall, different teaching styles have different advantages. To maximize high school students’ English learning engagement, teachers should pay a great attention to developing their own teaching styles of caring and sharing as well as rigorous and logical. Meanwhile, teachers should create a positive learning atmosphere by encouraging students to learn cooperatively, in the process of teaching.